2021
DOI: 10.3390/atmos12040450
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Contamination in Health Care Centers: Differences between Urban and Rural Settings

Abstract: This study aims to assess the airborne bioburden of rural and urban Portuguese Primary Health Care Centers (PHCC) using active and passive sampling methods and identify the potential differences in airborne microbiota between both environments. The highest total aerobic mesophilic bacterial load in indoor air were found in the Vaccination Room (448 CFU.m−3) in the Rural PHCC and in the Waiting Room (420 CFU.m−3) for Urban PHCC. The total coliforms contamination level in indoor air was detected only in the Clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 93 publications
(118 reference statements)
1
7
0
Order By: Relevance
“…The great adaptability of aerial microorganisms makes them capable of proliferating in any type of environment, whether it is near an industrial center, in the city center or in a green area on the outskirts of the urban nucleus [26] [27]. Also, the results shown a positive correlation between temperature and aerobic mesophilic bacteria concentration in the urban atmosphere, previously observed by Monteiro et al (2021) [28]. Most bacteria in our samples were Gram-negative, which have lower resistance to physical destruction or desiccation, compared with Gram-positive bacteria [29].…”
Section: Discussionsupporting
confidence: 59%
“…The great adaptability of aerial microorganisms makes them capable of proliferating in any type of environment, whether it is near an industrial center, in the city center or in a green area on the outskirts of the urban nucleus [26] [27]. Also, the results shown a positive correlation between temperature and aerobic mesophilic bacteria concentration in the urban atmosphere, previously observed by Monteiro et al (2021) [28]. Most bacteria in our samples were Gram-negative, which have lower resistance to physical destruction or desiccation, compared with Gram-positive bacteria [29].…”
Section: Discussionsupporting
confidence: 59%
“…The data from Portuguese studies revealed that Staphylococcus epidermidis [45] and Micrococcus spp. [45][46][47] were the most prevalent bacteria identified. However, S. epidermidis is not considered to be a relevant risk of exposure due to its lower infections rates [34].…”
Section: Discussionmentioning
confidence: 99%
“…However, S. epidermidis is not considered to be a relevant risk of exposure due to its lower infections rates [34]. On the other hand, Acinetobacter (species not identified) was found in two studies [32,34] as a prevalent genus in a university hospital from Ethiopia, justifying its persistence due to its great survival ability in the indoor environment [47], which can be a potential cause for hospital infections transmitted via the air [48]. Another relevant microorganism is Pantoea agglomerants, which is able to infect hospitalized individuals, particularly immunodeficient patients, through contaminated medical instruments [49].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of passive methods, such as the surface swabs used in this study, they allow to characterize the contamination over a longer period of time (after the last cleaning procedure), thus providing a more comprehensive picture of the real exposure [46][47][48][49]. Indeed, they have previously been used in several indoor environments [46,[51][52][53][54][55][56][57][58][59][60][61] generally providing more detailed and complete information regarding fungal species distribution. The use of both sampling methods allows to overcome each method limitation, ensuring a more precise exposure assessment [44].…”
Section: Discussionmentioning
confidence: 99%